The impact of salt concentration on the mineral nutrition of Tetragonia tetragonioides - Bekmirzaev, Gulom (2020)
The purpose of the experiment was to study the e ect of salinity (NaCl) on growth, biomass production (total yield), mineral composition (macro- and micronutrient contents in leaves and the soil in which the plant is grown) of Tetragonia tetragonioides during the vegetation period. The experimental work was conducted in the greenhouse at the University of Lille 1, France, from 2 November 2015 to 25 January 2016. Three salinity treatments (T1 (50 mM NaCl), T2 (100 mM NaCl), T3 (200 mM NaCl)) and a control treatment (T0 (0 mM NaCl)) were applied. Analysis of the results showed that the total yield of the crop had low variation between the salinity treatments and the control treatment. The salt concentrations had an e ect on the macro- and micronutrient contents in leaves and soil. In conclusion, T. tetragonioides exhibited good potential for use as a species to remove salt. This is the main important finding of this research.